Wages, Hiring Standards, and Firm Size - Weiss, Andrew; Landau, Henry J. (Journal of Labor Economics, 1984)
We present a model of firm behavior in which firms choose a wage and a hiring standard to maximize their profits. The correlation between productivity and reservation wage affects the relationship among firm size, wages, and hiring standards. In the special case where labor productivity is a linear function of a worker's reservation wage, we find that in the absence of hiring costs wages are monotonically increasing with firm size. Any positive hiring costs, however, result in an interval of sufficiently small firms within which wages decrease with firm size. In all cases, among sufficiently large firms, wages increase with firm size. A review of previous empirical evidence finds that in some occupations the relationship between wages and firm size is U-shaped, while in other occupations wages increase monotonically with firm size. These empirical findings are consistent with our theoretical results.